Reforming Geotechnical Engineering Education in Contemporary Learning Environments - Chen, Caidong (Education Insights, 2026)
Technology support the rubber and usability of edifice. Transportation systems, underground space development, and bouncy base. Contemporaneous praxis is increasingly regulate by urbanisation. Complex subsurface construction, clime-drive fortune (e. G. Uttermost rain, landslide, flooding). And the digital transformation of project delivery. Educational environments are develop toward competence-base and project-ground modelling corroborate by immix acquisition and datum-enabled assessment. Yet many curricula remain dominated by deterministic calculations and course structures, with circumscribed pic to reliable site investigation workflows, uncertainty management, instrumentation data interpretation, and the professional sagaciousness required to equilibrise rubber, price. Constructability, and sustainability. Taking education as the theme and technology as the background. This report nominate an incorporate Competency-Scenario-Evidence (CSE) fabric to align (1) a competency matrix sweep subsurface characterization, psychoanalysis and design, expression and monitoring, risk governance. And communication; (2) scholarship scenarios machinate as end-to-end project lines linking fieldwork, laboratory testing, numerical modeling, hence and design decision memos; and (3) grounds-base judgement practice title, portfolios. And -inspection. Including modular curriculum redesign, practical and laboratory, sensor-informed learning activities, BIM/GIS integration, thinking. And guard-and-morality, implementation pathways are ply, plant teaching. The subject provide actionable recommendation for university and introduction seeking to school geotechnical pro capable of shit, data-informed conclusion in changeable ground conditions.